Revitalizing the Acehnese Language through the “Cinta Bahasa Aceh” Instagram Community - Mukramah Mukramah; Sediken Tara Munthe (Academia Open, 2025)
General Background: The Acehnese language, as a crucial component of Indonesia’s linguistic and cultural diversity, faces a decline in daily use among teenagers due to modernization and the dominance of Indonesian and foreign languages. Specific Background: The emergence of social media platforms such as Instagram presents a new opportunity for language revitalization through interactive and youth-oriented digital content. Knowledge Gap: Despite the growing use of digital media in education, empirical studies examining its effectiveness in regional language revitalization remain limited. Aims: This study investigates the effectiveness of the “Cinta Bahasa Aceh” Instagram community in revitalizing the Acehnese language among adolescents. Results: Using a quasi-experimental design with 60 respondents, findings reveal significant improvement in vocabulary (32%), understanding of common expressions (28%), and conversational ability (35%) following a four-week digital intervention. Novelty: The study integrates Fishman’s Reversing Language Shift theory, Gilster’s digital literacy framework, and Rogers’ diffusion of innovation theory, highlighting Instagram as a participatory platform that transforms passive learners into active cultural agents. Implications: These results confirm that social media-based initiatives can serve as adaptive and replicable models for regional language preservation, offering both theoretical and practical contributions to the sustainability of linguistic heritage in the digital era. Highlights: Digital media effectively enhances youth engagement in language preservation. Instagram fosters active, participatory learning of regional languages. The study offers a replicable model for revitalizing endangered languages. Keywords: Language Revitalization, Digital Media, Instagram, Teenagers, Acehnese Language